An overview of the mechanistic approaches of antifungal nanomaterials - Saha, Sarmistha; Sachivkina, Nadezhda; Gurina, Regina; Neborak, Ekaterina; Zhabo, Natallia; Avdonina, Marina; Molchanova, Maria (Frontiers in Pharmacology, 2025)
Antifungal medications currently available on the market have significant drawbacks, including serious side effects and poor absorption. Nanotechnology offers a promising solution to address these issues. Metal nanoparticles, polymer nanoparticles, dendrimers, liposomes, and carbon quantum dots are often employed nano-delivery systems in antifungal therapy. While nanotechnology has several benefits, including improved oral bioavailability, less side effects, controlled release, and targeted delivery, it also has significant drawbacks. We reviewed the limitations of current commercial antifungal solutions, the primary mechanistic insights by which nanotechnology can enhance antifungal efficacy, and the challenges associated with these approaches. For optimum therapeutic interventions, modifying the surfaces of nanomaterials could be considered to improve their interaction with fungal cells. This can be achieved through targeted delivery to the fungal cell wall and membrane or by utilizing electrostatic interactions, which allow nanoparticles to effectively adhere to fungal cells. Additionally, custom-designed nanomaterials can overcome challenges posed by physiological barriers such as the blood-brain barrier, corneal barrier, and skin barrier. Despite the challenges of implementing nanotechnology in antifungal treatments, its potential and innovative applications open up new possibilities for effective antifungal therapies in the future.